EVALUATION EVALUASI APLIKASI PENDAFTARAN DAN KONSULTASI ONLINE NIMA MEDICAL AND REHABILITATION CENTER BERBASIS ANDROID MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) - Syarah Mazaya Fitriana (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
The development of information and communication technology has penetrated into the field of medical records, so that currently there are many health service facilities that use ICT to convert manual / paper medical records into electronic medical records. The Covid-19 pandemic brings a new trend in the world of health. Social restrictions on a large scale in order to suppress the transmission of this dangerous virus have changed the behavior of patients from many in-person examinations to electronic-based examinations. To measure the satisfaction and convenience of users of the Nima Medical and Rehabilitation Center application, the application needs to be evaluated in terms of ease of learning, ease of use, satisfaction and efficiency by using a questionnaire. The method used in measuring satisfaction is the usability scale system. The results of the assessment of the system usability scale method on the online registration and consultation application of the NIMA Medical And Rehabilitation Center received a score of 83 which means that this application is declared Acceptable, the grade scale is in category B, the Adjective rating is in the excellent category. In the assessment, the SUS Score Percentile Rank is in grade A so that this application can be used easily by users to get electronic-based consulting services and online registration.